Colonic Tuberculosis: a high Index of Suspicion - Wulyo Rajabto; M Usman SM; Khie Chen; Ari F Syam; Murdani Abdullah; Djumhana A; C Martin Rumende (The Indonesian Society for Digestive Endoscopy, 2005)
Tuberculosis remains to be one of the most common problems in developing countries such as Indonesia. It can involve many organs including gastrointestinal tract. Colonic tuberculosis is an ancient disease and has long been recognized. However, it is sometimes difficult to make early diagnosis due to nonspecific sign and symptoms. In endemic areas, correct diagnoses were made only 50% of the time. Without a high index of suspicion of the disease, it has been rarely diagnosed correctly. We reported a case of colonic tuberculosis in 18 years old female patient with lung tuberculosis.Endoscopic examination showed ulcerative mucosa, ‘halo lesion’, and pseudopolyp while PPD skin test, sputum smear and histopathological examination of endoscopic biopsy revealed negative for tuberculosis infection. The presence of lung tuberculosis had made high index of suspicion of colonic tuberculosis. Standard regimen of antituberculosis therapy was given and the patient showed good clinical response. Keywords: high index suspicion, colonic tuberculosis